Let's go 2; student book / Ritsuko Nakata; Karen Frazier; Barbara Hoskins - Nakata, Ritsuko; Frazier, Karen; Hoskins, Barbara (Estados Unidos de América, 2006)
Let's Go 2 Student Book with CD: Language Level: Beginning to High Intermediate. Interest Leve
Incluye: bibliografía, imagen, índice onomástico
Col. OGenCol. OGen|}
Keywords: 1. OBRAS GENERALES 2. VOCABULARIO 3. LENGUAJE-APRENDIZAJE